2005
DOI: 10.1021/es0405171
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Microextraction Measurement of Parent and Alkyl Polycyclic Aromatic Hydrocarbons in Milliliter Sediment Pore Water Samples and Determination of KDOC Values

Abstract: The U.S. Environmental Protection Agency (EPA) narcosis model for benthic organisms in polycyclic aromatic hydrocarbon (PAH) contaminated sediments requires the measurement of 18 parent PAHs and 16 groups of alkyl PAHs ("34" PAHs) in pore water with desired detection limits as low as nanograms per liter. Solid-phase microextraction (SPME) with gas chromatographic/mass spectrometric (GC/ MS) analysis can achieve such detection limits in small water samples, which greatly reduces the quantity of sediment pore wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
149
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(155 citation statements)
references
References 16 publications
6
149
0
Order By: Relevance
“…Ter-Laak, Agbo, Barendregt, and Hermens (2006) examined the use of solid-phase extraction (SPE) in measuring freely dissolved concentrations of PAHs in soil pore water. Some researchers have suggested that solid-phase microextraction (SPME) with gas chromatographic/mass spectrometric (GC/MS) analysis can achieve detection limit as low as nanograms per litre of PAHs and alkyl PAHs in sediment pore water (Hawthorne, Grabanski, Miller, & Kreitinge, 2005). In soil samples, high resolution gas chromatography-mass spectrometry (HRGC-MS) and liquid chromatography-fluorescence detection (LC-FD) have been applied successfully in measuring the final concentrations of PAHs (Berset, Ejem, Holzer, & Lischer, 1999).…”
Section: Determination Of Pahsmentioning
confidence: 99%
“…Ter-Laak, Agbo, Barendregt, and Hermens (2006) examined the use of solid-phase extraction (SPE) in measuring freely dissolved concentrations of PAHs in soil pore water. Some researchers have suggested that solid-phase microextraction (SPME) with gas chromatographic/mass spectrometric (GC/MS) analysis can achieve detection limit as low as nanograms per litre of PAHs and alkyl PAHs in sediment pore water (Hawthorne, Grabanski, Miller, & Kreitinge, 2005). In soil samples, high resolution gas chromatography-mass spectrometry (HRGC-MS) and liquid chromatography-fluorescence detection (LC-FD) have been applied successfully in measuring the final concentrations of PAHs (Berset, Ejem, Holzer, & Lischer, 1999).…”
Section: Determination Of Pahsmentioning
confidence: 99%
“…These effects complicate the analysis of porewater concentrations even in carefully controlled laboratory studies such as those conducted by Lu et al (2003 2 and 2004 3 ) and make practical routine determination of porewater concentrations exceedingly difficult. Hawthorne et al (2005) 9 demonstrated an approach for the measurement of porewater concentration requiring only a small water volume under controlled laboratory conditions as long as the colloidal particles and associated contaminants could be separated from the sample. This method employs polydimethylsiloxane (PDMS) to extract and concentrate the sample (ex-situ, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…in whole sediments) solid phase microextraction (SPME) technique. The use of SPME has also been employed in laboratory evaluations of porewater concentrations in whole sediments, including by Meyer et al (2000) 10 , Conder et al (2003) 11 , and Hawthorne et al (2005) 9 . The focus herein is primarily to evaluate the applicability of the approach to in-sediment (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Further details on the SPME method can be found in Hawthorne et al, 2005 (also in US EPA Method 8272). To verify the SPME technique used for sediment batch experiments, liquid-liquid extraction with hexane was also performed.…”
Section: Methodsmentioning
confidence: 99%